STRESS, ANXIETY, AND DEPRESSION IN STOMATITIS PATHOGENESIS: A SYSTEMATIC REVIEW - Cahyono, Bagus Dwi; Huda, Nurul; Aristawati, Evy; Aditya, Ronal Surya; Rahmawati, Apriana; Kusuma, Erik; Nasriati, Ririn (Journal of Vocational Nursing, 2025)
Introduction: Recurrent Aphthous Stomatitis (RAS) is a chronic inflammatory condition characterized by painful ulcers on the oral mucosa. Emerging evidence indicates that psychological factors, such as stress, anxiety, and depression, may play a role in its development. This review aims to examine the influence of these mental health factors on the onset and progression of RAS based on recent scientific literature. Methods: he exact mechanisms through which psychological stressors contribute to RAS remain poorly understood. To address this, a systematic review was conducted following PRISMA guidelines to consolidate current research findings. A thorough search was performed across PubMed, the Cochrane Library, and Google Scholar to identify original studies published within the past decade. The search terms used were: ("Recurrent Aphthous Stomatitis" OR "RAS") AND ("Stress" OR "Anxiety" OR "Depression") AND ("Psychological Factors" OR "Mental Health"). Results: Findings from the reviewed literature indicate a strong correlation between stress and both the initiation and recurrence of RAS. This association appears to be largely driven by the activation of the hypothalamic–pituitary–adrenal (HPA) axis, resulting in increased cortisol levels and subsequent suppression of immune function. These physiological changes are believed to weaken mucosal defenses, thereby increasing vulnerability to ulcer formation. Conclusions: These insights underscore the importance of incorporating psychological interventions—particularly stress-reduction techniques—into the management of RAS to enhance patient well-being and reduce symptom burden.